Validity evidence of procedural tactical knowledge test for sports guidance - GRECO, Pablo Juan; PEREZ MORALES, Juan Carlos; ABURACHID, Layla Maria Campos; SILVA, Schelyne Ribas da (Brazilian journal of physical education and sport, 2015)
This study aimed to investigate the evidence validate content, construct and test the reliability of procedural tactical knowledge for sporting orientation (TCTP: OE) of children and youth in sports games collective invasion (basketball, futsal and handball). In the process of content validity participated as judges 11 technicians, and 3 basketball, 4-five side indoor football, and 4 handball. In empirical procedures to sample comprised a total of 570 participants. The average age of study participants was 10.32 ± 1.45 years. Content validity was determined by calculating the coefficient of content validity (CVC). We used exploratory factor analysis (EFA) for construct validity. The method used was principal components with Varimax orthogonal rotation and Kaiser normalization. The reliability of the TCTP: EO was established through the test-retest method on different days. The technique used was the intraclass correlation (ICC). Regarding content validity of the CVC calculated for clarity of language (CVCt = 0.83), practical relevance (CVCt = 0.91) and theoretical relevance (CVCt = 0.95) was satisfactory. Factor analysis confirmed the structure of the final model with two factors, called attack and defense, explaining in all cases over 66% of the variance. Regarding the reliability of the instrument TCTP: OE showed satisfactory values and excellent (ICC ≥ 0.4). We conclude that the TCTP: OE enables the evaluation of the player is with hand / foot, which determines an assessment consistent with current precepts of sport initiation.